Adolescent sexual behaviour in a refugee setting in Uganda - Bukuluki, Paul (Reprod Health, 2021)
BACKGROUND: Children under 18 years old constituted more than half (52%) of the refugee population in 2017. Adolescent Sexual and reproductive health is an essential component of primary health care. Yet, not every refugee adolescent is able to access sexual and reproductive health services. METHODS: Using quantitative data from 356 refugee adolescents and qualitative data (17 in-depth interviews and nine key informant interviews), we examine refugee adolescent sexual behaviour in Bidibidi settlement—the largest refugee settlement in Uganda using a binary logistic regression model. RESULTS: The results show that 25% of refugee adolescents in Bidibidi refugee settlement had ever had sex. After controlling for all factors, results show that refugee adolescents aged 16–18 years (OR  =  3.47; 95% CI  =  1.09–10.94), males (OR  =  17.59; 95% CI  =  4.48–69.07), not in school (OR  =  14.57; 95% CI  =  2.20–96.35) were more likely to engage in sexual behaviour than their counterparts. Refugee adolescents who do not agree that a girl cannot get pregnant if she has sex while standing up (knowledge about getting pregnant) were significantly less associated with sexual behaviour (OR  =  0.30; 95% CI  =  0.10–0.85). CONCLUSIONS: Results from this study show that keeping refugee adolescents in school and providing sexual and reproductive health information are likely to delay refugee adolescents’ engagement in sexual behaviour. Therefore, there is need to promote keeping refugee adolescents in school in order to improve sexual and reproductive health of adolescent refugees living in low-income countries such as Uganda.